Cladocerans from gut contents of fishes associated to macrophytes from Taquari River Basin, MS, Brazil - Güntzel,Adriana Maria (2012)
AIM: The aim of this study was to identify the cladocerans species from the gut contents of fishes sampled in an oxbow lake from Taquari River Basin, MS, with the specific view of investigating the importance of these crustaceans in the fishes diets; METHODS: Sampling was carried out in April and August of 2005 (dry season) and January of 2006 (wet season). The fish were captured with a sieve. In the laboratory, individuals were identified and stomachs were removed and weighed. The stomach contents were identified, and a Feeding Index calculated; RESULTS: The items most consumed by fishes were filamentous algae, Cladocera and detritus. The Cladocera were especially important in the August and January samples, and consisted primarily of Chydoridae; cladocerans were most consumed by species of Serrapinnus and by Mesonauta festivus. Fish fed more in April, with decreases occurring in stomach fullness on the other two sampling dates. CONCLUSIONS: Cladocerans associated with macrophytes may be an important food source for small fish individuals in marginal lakes from Taquari River Basin. The relative importance of the Chydoridae in the guts may have been due to the high relative abundance and species richness of this group in the environment. A short discussion on fish feeding habits was included in the text.